Scenario-based decision support for an integrated management of water resources. Issue 4 (2nd October 2017) - Dessie, Mekete; Verhoest, Niko E. C.; Adgo, Enyew; Poesen, Jean; Nyssen, Jan
ABSTRACT: In this study, analyses of future scenarios of water demand and supply as well as an assessment of trade-offs for water allocation across the different water use sectors in the upper Blue Nile basin are made. Different periods of regulation of Lake Tana (Ethiopia) and subsequent impacts on the lake level hydrological regime are investigated. A decision support system is developed and available water supply for normal- and low-flow hydrological conditions are determined based on recorded flow data and a simple rainfall-runoff model. Different scenarios have been triggered and simulations are conducted to understand the implications of planned water resource developments in the area. We found that the annual inflows to Lake Tana under an average hydrological condition are about 5.7 × 10 9  m 3 and are estimated to reduce by about 27% when all planned water resources development projects are implemented in the catchment. These projects aim at the generation of 460 MW hydroelectric power and about a billion m 3 per annum supply of water to the large-scale irrigation schemes. During low-flow conditions, supply will run short of demands and the lake water level can drop by 0.3 m from the natural outlet level (1785 m a.s.l). Lake water levels and long-term lake level fluctuations have been affected significantly due to regulation with subsequent impacts on the lake ecology. An upstream–downstream cooperation, transparency and participation in the decision making and establishment of an adequate data acquisition system are critically important elements in the management of water resources in the basin.